Circulating miRNAs as potential molecular biomarker of early pregnancy in ewes - Kose, M.; Kaya, M. S.; Kirbas, M.; Dursun, S.; Hitit, M.; Alak, I.; Atli, M. O. (Wiley, 2018)
22nd Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) -- SEP 27-29, 2018 -- Cordoba, SPAIN

European Soc Domest Anim Reprod

Supported by TUBITAK 214O643.

[Abstract Not Available]

WOS:000445201100232

TUBITAK [214O643]
Keywords: [No Keyword]